PENGARUH LAMA PENYIMPANAN DAN KONSENTRASI Bifidobacterium BBIV PADA YOGHURT TERHADAP KADAR ASAM LAKTAT - Hafidh Syaifuddin; Dyah Fitri Kusharyati; Pancrasia Maria Hendrati (Scripta Biologica, 2014)
Yogurt is a well-known fermented dairy product. The addition of Bifidobacterium BBIV into yogurt was able to increase the content of lactic acid and therefore was able to inhibit the growth of Salmonella typhi. This study aimed to find out the amount of lactic acid in yogurt added by the culture of Bifidobacterium BBIV in the various concentration and storage periods; to evaluate antibacterial activity against Salmonella typhi. This research was experimental using a Completely Randomized Design. The proportion of the combination of Bifidobacterium BBIV starter (Lactobacillus bulgaricus: Streptococcus thermophillus: Bifidobacterium BBIV) were 1:1:0 (B0), 1:1:0,5 (B1), 1:1:1 (B2) and 1:1:1,5 (B3). The storage period was 30-days, observations were made every five days. This study computed the ANOVA followed by the LSD test for data analysis. The result showed that the addition of Bifidobacterium BBIV starter in various proportion to the yogurt with the different storage periods gave significantly different effects on the lactic acid amount. The addition of Bifidobacterium BBIV starter of 1:1:1(B2) proportion stored after 20 days showed an increasing level of lactic acid. All of the yogurt with any other ratios (B0, B1, B2, and B3) of Bifidobacterium BBIV starter, stored after 30 days were still able to inhibit the growth of Salmonella typhi. The organoleptic test showed that yogurt with 1:1:1,5 (B3) starter ratio was the most preferred in both taste, aroma, color, and homogeneity. The study suggested that the amount of lactic acid in the yogurt increased by the addition of Bifidobacterium BBIV in various ratios, i.e., 1:1:0,5; 1:1:1; and 1:1:1,5 after 30 days were 1,2652%;1,2243% and 1,2506% respectively. The inhibition zone produced by yogurt on the bacterial growth of Salmonella typhi was 6,5–8,3 millimeters in any of the storage periods.